2019
DOI: 10.1111/1471-0528.15882
|View full text |Cite
|
Sign up to set email alerts
|

The hologenome concept of evolution: do mothers matter most?

Abstract: The hologenome concept of evolution is discussed, with special emphasis placed upon the microbiome of women. The microbiome is dynamic, changing under different conditions, and differs between women and men. Genetic variation occurs not only in the host, but also in the microbiome by the acquisition of novel microbes, the amplification of specific microbes, and horizontal gene transfer. The majority of unique genes in human holobionts are found in microbiomes, and mothers are responsible for transferring most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…HGT is an essential evolutionary tool and was thought to be limited to prokaryotes, but over the past decade, increasing evidence indicates genetic materials are exchanged between prokaryotes and eukaryotes (both endosymbionts and free-living organisms) [ 43 , 44 , 45 ]. The absence of tnaA in the genomes of vertebrates, including mammals, indicates the need for tryptophan degradation has reduced and that the function is largely provided by gut microbes as a result of co-evolution in a holobiont [ 46 ]. However, vertebrates have also adopted other means of tryptophan degradation via the kynurenine pathway by cleaving the indole moiety with tryptophan 2,3-dioxygenase in the liver [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HGT is an essential evolutionary tool and was thought to be limited to prokaryotes, but over the past decade, increasing evidence indicates genetic materials are exchanged between prokaryotes and eukaryotes (both endosymbionts and free-living organisms) [ 43 , 44 , 45 ]. The absence of tnaA in the genomes of vertebrates, including mammals, indicates the need for tryptophan degradation has reduced and that the function is largely provided by gut microbes as a result of co-evolution in a holobiont [ 46 ]. However, vertebrates have also adopted other means of tryptophan degradation via the kynurenine pathway by cleaving the indole moiety with tryptophan 2,3-dioxygenase in the liver [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that about 145 genes in man originated from bacteria, including a few involved in amino-acid metabolism acquired by HGT [ 46 ]. For instance, Maximum Likelihood and Bayesian phylogenetic methods showed that eukaryotic pyruvate formate lyase, a homolog of the firmicutes gene, may have been acquired through HGT [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the general assumptions of the hologenome concept, however, is that both the host genome and the genetic information of the associated microbiome are transferred from one generation to the next. This postulation underlies the critical role of mothers in transferring microorganisms to their offspring ( 34 ), a challenging process for our model organism that has highly dispersive planktonic larval stages followed by a recruitment phase. Another crucial result is that fungal communities are exclusive to the environmental matrices while almost absent in C. haematocheir organs.…”
Section: Discussionmentioning
confidence: 99%
“…Within the concept of our classical western medicine, these elements can be regulatory systems (microbiota, enteroendocrine regulation, neurohormonal regulation, natural immune regulation, and finally, at the top of the pentagram, the overall genomic regulation controlling the developmental and integrity status of the organism). Inclusion of microbiota among the systems regulating and controlling the physiological status of the host further justifies creation of the holobiont concept introduced into the scientific literature by Linn Margulis, which was at that time elaborated into a system for defining itself and the concept of hologenome as one of the tools of evolution (93)(94)(95)(96)(97). The analyses performed to date demonstrate the importance of maintaining a dynamic equilibrium of bacterial species in the intestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%